The role of Bach1 in regulating oxidative stress in HaCaT cells - ZOU Hui; CHEN Jiaoquan; OU Shanshan; LIN Tianyi; CHEN Ziyan; LI Huaping; LI Runxiang; PENG Liqian; ZHU Huilan (Pifu-xingbing zhenliaoxue zazhi)
[Objective] To explore the regulatory mechanism of Bach1 on downstream antioxidant target genes and its role in protecting against damage-induced by oxidative stress. [Methods] The Bach1 overexpression and knockdown clones were successfully constructed, and the HaCaT integrated strains, Bach1 knockdown group (Bach1-shRNA) and Bach1 overexpression group (Bach1-OE), were constructed using lentivirus packaging. Meanwhile, the corresponding control group, Bach1 knockdown control group (KD-control) and Bach1 overexpression control group (OE-control), were constructed. RT-qPCR and Western blotting were used to assess the knockdown and overexpression efficiency of Bach1, and the expression levels of downstream antioxidant target genes, including HO1, CAT, GPX and SOD. An oxidative stress model was established by treating HaCaT cells with various concentrations of H2O2. The cell viability was detected using CCK8. In addition, the ROS levels were detected by flow cytometry following the treatment of cells with either H2O2 or UVB. [Results] The expression levels of Bach1 mRNA and protein were decreased significantly in Bach1-shRNA group compared with the KD-control group (both P<0.01), while the levels of Bach1 mRNA and protein were significantly higher in the Bach1-OE group than in the OE-control (both P<0.01). Compared to the KD-control group, the Bach1-shRNA group exhibited a significant increase in the expression levels of HO-1 mRNA (t=7.66, P<0.01), but a significant decrease in the expression levels of mRNA for CAT, GPX, and SOD (all P<0.01). CCK8 assay revealed that 0~250 μM of H2O2 did not significantly change the viability of wild-type HaCaT cells. However, cell viability was decreased significantly after the treatment with 300 μM of H2O2 (P<0.001). Treatment with either 250 μM H2O2 or 300 mJ/cm2 UVB significantly increased the ROS levels in the Bach1-shRNA group compared to the KD-control group (t=40.12, 52.41, respectively, both P<0.001), but the ROS levels were lower in the Bach1-OE group than in the OE-control group (t=4.85, 59.49, respectively, both P<0.01). [Conclusions] Downregulation of Bach1 increases oxidative stress, while overexpression of Bach1 decreases oxidative stress in HaCaT cells.